2011
DOI: 10.5089/9781463923259.001
|View full text |Cite
|
Sign up to set email alerts
|

Do Remittances Reduce Aid Dependency?

Abstract: Aid has been for decades an important source of financing for developing countries, but more recently remittance flows have increased rapidly and are beginning to dwarf aid flows. This paper investigates how remittances affect aid flows, and how this relationship varies depending on the channel of transmission from remittances to aid. Buoyant remittances could reduce aid needs when human capital improves and private investment takes off. Absent these, aid flows could still drop as remittances may dampen donors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…In this study, we expect that donors allocate more aid to reward countries for the good quality of their economic policies, in particular their trade liberalization policies. Lastly, a number of past studies analyzed the relationship between aid and remittances, and found that development aid acts as a complement to remittances [18,89,90]. By improving household capacity to invest in education and healthcare, remittance does improve the recipient country's absorption capacity, the lack of which has been often pointed out as a bottleneck to aid scaling up.…”
Section: Data Descriptionmentioning
confidence: 99%
“…In this study, we expect that donors allocate more aid to reward countries for the good quality of their economic policies, in particular their trade liberalization policies. Lastly, a number of past studies analyzed the relationship between aid and remittances, and found that development aid acts as a complement to remittances [18,89,90]. By improving household capacity to invest in education and healthcare, remittance does improve the recipient country's absorption capacity, the lack of which has been often pointed out as a bottleneck to aid scaling up.…”
Section: Data Descriptionmentioning
confidence: 99%